Defining Environments: Understanding Architectural Performance through Modelling, Simulation and Visualisation. (3rd January 2018) - Peters, Brady
Abstract : Largely due to environmental concerns, approaches to architecture are becoming increasingly crossdisciplinary. With this comes a need for ever more integrated digital simulation tools.Brady Peters – Assistant Professor at the University of Toronto and a Director of Smartgeometry, an organisation that promotes computation in architecture – discusses what these tools can achieve, and highlights two companies that are pioneering their use and development: Danish architecture firm BIG, and international engineers BuroHappold. They set out to visualise not only 'hard metrics' such as energy consumption, but also 'soft metrics' like wellbeing and productivity.